2002
DOI: 10.1177/1368430202005001807
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Employee Participation: Attitudes and Perceptions in Trainees, Employees and Teams

Abstract: Research in employee participation has tended to focus on participation outcomes rather than the process of successful implementation, and to evaluate program success in terms of (a) employee attitudes (e.g. satisfaction) post-participation and (b) productivity or effectiveness. We argue that such approaches ignore the process component of successful implementation such as the long-term maintenance of interest in and support for participation among employees. A second problem is that although some research con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 122 publications
1
11
0
Order By: Relevance
“…Teamworking means groups having common valued goals, multiple tasks and complementary skills, internal interdependence and coordination, being mutually accountable for methods, resource use and outcomes, and taking on extended (managerial) responsibility. Originally, their growth was on the basis of sociotechnical systems theory (Langan-Fox, 2003;Langan-Fox, Code, Gray, & Langfield-Smith, 2002) and quality of work life movements, followed by stagnation in the 1980s. They have had a renaissance in application and research in the past 15 years, within safety-critical industries, manufacturing, the military, and the service sector (Genaidy, Karwowski, Succop, Kwon, & Alhemoud, 2000;Zolnierczyk-Zreda, 2000).…”
Section: Team Mental Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Teamworking means groups having common valued goals, multiple tasks and complementary skills, internal interdependence and coordination, being mutually accountable for methods, resource use and outcomes, and taking on extended (managerial) responsibility. Originally, their growth was on the basis of sociotechnical systems theory (Langan-Fox, 2003;Langan-Fox, Code, Gray, & Langfield-Smith, 2002) and quality of work life movements, followed by stagnation in the 1980s. They have had a renaissance in application and research in the past 15 years, within safety-critical industries, manufacturing, the military, and the service sector (Genaidy, Karwowski, Succop, Kwon, & Alhemoud, 2000;Zolnierczyk-Zreda, 2000).…”
Section: Team Mental Modelsmentioning
confidence: 99%
“…Too often, research tends to focus on outcomes rather than processes (Langan-Fox, Armstrong, Anglim, & Balvin, 2002;Langan-Fox, Code, Gray, & Langfield-Smith, 2002). Likewise, it is important to understand the process through which TMMs develop and are modified.…”
Section: Team Developmentmentioning
confidence: 99%
“…However, several pieces of evidence indicate that there is a need to better understand these processes. There is some direct evidence of inter-participant variability in perceptions of interventions: this suggests that employees actively appraise the interventions they experience (Kompier & Kristensen, 2001;Kompier, Cooper, & Geurts, 2000;Langan-Fox, Code, Gray, & Langfield-Smith, 2002). This could be important because perception and appraisal play such a crucial role in validated models of work stress and models of change in health behaviour (Ajzen, 1991;Lazarus, 1966;Lazarus & Folkman, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…However, participants' direct appraisals of the sufficiency of the intervention content have rarely been investigated. Moreover, these appraisals may function as part of a mediating mechanism between participation and intervention outcomes (Eklöf, Ingelgård, & Hagberg, 2004;Langan-Fox et al, 2002). For example, participants whose active appraisal of an intervention leads to the view that the intervention was weak may report less change in the outcome measures than those whose active appraisal led them to the view that the same intervention was of high quality.…”
Section: Introductionmentioning
confidence: 99%
“…As has been pointed out (Minkler and Pies, 1999), behind the euphemism of participation, the realities of power imbalances often remain. For example, Langan-Fox et al (2002) found that participation in an employee participation program was likely to be affected by organizational seniority. There are no apparent solutions to this dilemma.…”
Section: Discussionmentioning
confidence: 99%